Anti-fibrotic Effects of Cardiac Progenitor Cells in a 3D-Model of Human Cardiac Fibrosis - Bracco Gartner, Tom C. L.; Deddens, Janine C.; Mol, Emma A.; Magin Ferrer, Marina; van Laake, Linda W.; Bouten, Carlijn V. C.; Khademhosseini, Ali; Doevendans, Pieter A.; Suyker, Willem J. L.; Sluijter, Joost P. G.; Hjortnaes, Jesper (Frontiers in Cardiovascular Medicine, 2019)
Cardiac fibroblasts play a key role in chronic heart failure. The conversion from cardiac fibroblast to myofibroblast as a result of cardiac injury, will lead to excessive matrix deposition and a perpetuation of pro-fibrotic signaling. Cardiac cell therapy for chronic heart failure may be able to target fibroblast behavior in a paracrine fashion. However, no reliable human fibrotic tissue model exists to evaluate this potential effect of cardiac cell therapy. Using a gelatin methacryloyl hydrogel and human fetal cardiac fibroblasts (hfCF), we created a 3D in vitro model of human cardiac fibrosis. This model was used to study the possibility to modulate cellular fibrotic responses. Our approach demonstrated paracrine inhibitory effects of cardiac progenitor cells (CPC) on both cardiac fibroblast activation and collagen synthesis in vitro and revealed that continuous cross-talk between hfCF and CPC seems to be indispensable for the observed anti-fibrotic effect.